Simulation of Net Primary Production (NPP) of Picea abies in southern Sweden - Subramanian, Narayanan (2011)
The potential Net Primary Production (NPP) under climate change was simulated by using two process based growth models, 3-PG and BIOMASS. Both models were run for two climate scenarios A2 and B2 during the period 2071-2100 and compared with simulations of reference climate (1961-1990). The simulated NPP of the 3-PG model was also compared with simulated output of NPP from the BIOMASS model, for Picea abies (Norway spruce) at Asa in southern Sweden. In addition, the simulation results from 3-PG were compared with the biomass production of the empirical growth model DT. Special objectives of this study were (i) to estimate 3-PG parameters for Picea abies, (ii) compare the simulated NPP under different climate scenarios A2 and B2, (iii) analyze the 3-PG model sensitivity towards change in temperature, rainfall and soil fertility and (iv) to compare the prediction of potential NPP between 3-PG and BIOMASS models. Climate data showed an increased precipitation during winter season and elevated temperature throughout the whole year. The development of dry mass (tones/ha) simulated through 3-PG had good correlation with values simulated through DT. The R2 value for foliage dry mass, root dry mass, stem dry mass and total dry mass are 0.82, 0.94, 0.7 and 0.73 respectively. The relative increase in predicted NPP ranged between 26.8-48.4% and 55.5-101.6% for A2 and B2 scenarios, respectively. A sensitivity analysis was also conducted for the effect of rainfall, temperature and soil fertility on potential NPP simulated by the 3-PG model. The relative range of NPP under A2-scenario was 55.5-101.6% for the 3-PG model and 13.3-41.8 for the BIOMASS model. The corresponding value for the B2-scenario was 26.8-48.4 % for 3-PG and 10.7-29.7 for BIOMASS.